2021
DOI: 10.14710/ik.ijms.26.2.79-86
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Heavy Metals (Pb and Cu) at Tin Sea Mining Field and Its Impact to Marine Tourism and Fisheries

Abstract: The dynamics of heavy metals (Pb and Cu) distribution near sea mining locations can show a negative impact on fisheries resource management. The study was conducted at the coastal area of Tanah Merah Beach, Central Bangka Regency, the geographical location at 02o12'50 "S and 106o13'00" E. This study aims to determine the extent of heavy metals (Pb and Cu) distribution adjacent sea mining field and its impact on marine tourism and fisheries. Purposive sampling method was used to identify the sampling locations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Selain itu, belum ada penelitian dan publikasi terkait kontaminasi mikroplastik pada kerang di perairan Pulau Bangka. Penelitian yang telah dilakukan, sebatas mengkaji potensi kontaminasi logam berat terhadap komoditi perikanan termasuk kerang (Hindarti et al, 2008;Adibrata et al, 2021), kandungan total bakteri kerang darah (Anadara granosa L) hasil budidaya yang melebihi standar PerKa BPOM No. 16 tahun 2016 (Pratiwi dan Sari, 2019).…”
Section: Pendahuluanunclassified
“…Selain itu, belum ada penelitian dan publikasi terkait kontaminasi mikroplastik pada kerang di perairan Pulau Bangka. Penelitian yang telah dilakukan, sebatas mengkaji potensi kontaminasi logam berat terhadap komoditi perikanan termasuk kerang (Hindarti et al, 2008;Adibrata et al, 2021), kandungan total bakteri kerang darah (Anadara granosa L) hasil budidaya yang melebihi standar PerKa BPOM No. 16 tahun 2016 (Pratiwi dan Sari, 2019).…”
Section: Pendahuluanunclassified
“…The Bangka Belitung Islands Province is one of the world's tin producers (Maia et al, 2019). However, the presence of tin mining has a significant impact on the degradation of coastal ecosystems (Adibrata et al, 2021), especially mangrove forest ecosystems (Sari et al, 2023), and biodiversity (Hasan et al, 2023a;Syarif et al, 2023a;Valen et al, 2023;Kusumah et al, 2023). The area of mangrove forests on the east coast of Bangka Island decreased, from 1, 104.3 hectares (2002) to 964.4 hectares (2017) (Savira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining tin mining activities produce tailings that are released into the waters. Waste from mining activities is generally in the form of waste containing heavy metals (Adibrata et al, 2021;Bidayani and Reniati, 2021). Tin mining waste, whether from large-scale industrial operations like suction boats and dredges or from small-scale unconventional mining (TI), has high concentrations of heavy metals, specifically lead (Pb), cadmium (Cd), zinc (Zn) and Chromium (Cr) (Okewale and Grobler, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies showed the adverse impact of mining activity waste on water quality (Muslih et al, 2014;Komalasari et al, 2019;Adibrata et al, 2021). High turbidity reduces dissolved oxygen (DO) levels and water clarity, thereby slowing down photosynthesis in water.…”
Section: Introductionmentioning
confidence: 99%